Biological Suppression of Populations of Heterodera schachtii Adapted to Different Host Genotypes of Sugar Beet - Eberlein, Caroline; Heuer, Holger; Westphal, Andreas (Frontiers in Plant Science, 2020)
Productivity of sugar beet and brassica vegetable crops is constrained by the nematode Heterodera schachtii worldwide. In sugar beet cropping areas of Central Europe and North America, H. schachtii is managed by crop rotation, and cultivation of resistant brassica cover crops. The recently released nematode-tolerant sugar beet cultivars suffer less damage than susceptible cultivars at high initial population densities of H. schachtii. Many tolerant cultivars allow for less nematode reproduction than susceptible cultivars. Monoculture of susceptible hosts can facilitate the evolution of suppressive soil. Objectives of this study were to determine if susceptible hosts are required for this process, and if monoculture with sugar beet genotypes of different host status (susceptible, resistant, tolerant) impact this capacity. Additionally, we tested if amending soil with the cyst nematode pathogens P. nishizawae or Hyalorbilia sp. strain UCRDo50 favored the establishment of soil suppressiveness. In four-year microplot studies with H. schachtii Schach0 or Schach1, one susceptible, one Schach0-resistant and one tolerant sugar beet genotype were monocultured. In 2010, plots were amended with P. nishizawae or UCRDo50, the last being introduced into non-treated soil for Schach0, and into previously biocide-treated soil for Schach1. In 2011, respective Schach0 plots received a second amendment with UCRDo50. Nematode population densities and growth and yield parameters were determined annually. Effects of P. nishizawae and UCRDo50 on populations of H. schachtii were limited and not consistent. Starting in the second year of the monoculture, eggs of both H. schachtii pathotypes became diseased. Up to 90% of the total eggs were encumbered by the third cropping cycle, under the susceptible, resistant and tolerant cultivar. In all years, the tolerant genotype produced the highest and most stable white sugar yields while yields of the other cultivars slowly improved during the monoculture. Results of this study suggested the presence of egg-infecting factors in this sugar beet monoculture that dramatically increased the proportions of diseased eggs. The tolerant cultivar allowed establishment of soil suppressiveness without the initial yield decline observed when susceptible crops are grown in monoculture.